Integrasi Teori Governance Stoker dengan Pendekatan Sosiologi Politik dalam Menganalisis Efektivitas Kebijakan Desentralisasi di Indonesia - Ahyar, Usep Saepul; Khoirurrosyidin; Darmanto Saputro (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This article analyzes the integration of Stoker’s governance theory with a political sociology approach in examining the effectiveness of decentralization policy in Indonesia. Using qualitative-descriptive methods and literature study, this research finds that Stoker’s five governance propositions (diffusion of accountability, blurred institutional boundaries, power shifts, the use of autonomous self-governing networks, and the state’s capacity to act without commanding) provide a relevant framework for analyzing decentralization effectiveness. When combined with a political sociology approach emphasizing political culture, social capital, and elite relations, a more comprehensive analytical framework emerges. The findings indicate that the effectiveness of decentralization in Indonesia is significantly influenced by local political dynamics, intergovernmental relations, and bureaucratic capacity. The research recommends institutional strengthening at the regional level and improved central-regional coordination.